2023
DOI: 10.1021/acs.langmuir.2c02905
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Microscale Droplet Generation and Manipulation

Abstract: Microscale droplet generation and manipulation have widespread applications in numerous fields, from biochemical assays to printing and additive manufacturing. There are several techniques for droplet handling. Most techniques, however, can generate and work with only a limited range of droplet sizes. Furthermore, there are constraints regarding the workable variety of fluid properties (e.g., viscosity, surface tension, mass loading, etc.). Recent works have focused on developing techniques to overcome these l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 145 publications
0
12
0
Order By: Relevance
“…To verify whether the ink can be adequately ejected, we studied the ejection behavior of the ink drop by designing four trapezoidal waveforms, A, B, C, and D (Figure ). Figure shows the ink drop formation stage for inks B1 and B2 under waveforms A, B, C, and D (B1–A, B1–B, B1–C, B1–D, B2-A, B2–B, B2–C, and B2–D). The formation of ink drops has three stages: (1) a meniscus-shaped liquid interface formed at the nozzle opening; (2) the ink drop ligament is gradually elongated until it breaks from the nozzle; (3) during the fall of the ink drop ligament, the ligament splits into primary and secondary ink drops, and then the primary ink drop and the secondary ink drops are merged into the stable ink drop.…”
Section: Resultsmentioning
confidence: 99%
“…To verify whether the ink can be adequately ejected, we studied the ejection behavior of the ink drop by designing four trapezoidal waveforms, A, B, C, and D (Figure ). Figure shows the ink drop formation stage for inks B1 and B2 under waveforms A, B, C, and D (B1–A, B1–B, B1–C, B1–D, B2-A, B2–B, B2–C, and B2–D). The formation of ink drops has three stages: (1) a meniscus-shaped liquid interface formed at the nozzle opening; (2) the ink drop ligament is gradually elongated until it breaks from the nozzle; (3) during the fall of the ink drop ligament, the ligament splits into primary and secondary ink drops, and then the primary ink drop and the secondary ink drops are merged into the stable ink drop.…”
Section: Resultsmentioning
confidence: 99%
“…[117][118][119] In microfluidic channels, droplet formation under continuous flow typically involves the manipulation of immiscible phases, such as water and oil, at microfluidic junctions and flow-focusing geometries. [120][121][122] For single-cell workflows, this method is used to encapsulate individual cells in monodisperse droplets ranging from femtoliters to nanoliters, often termed "microdroplets". Once single cells are encapsulated in microdroplets, they can be sorted into various outlets for downstream cell culture and/or characterization.…”
Section: Droplet-based Microfluidicsmentioning
confidence: 99%
“…Nowadays, advancement in microfabrication techniques of various materials has enabled the precise design and modulation of structural features, pressure, and boundary conditions, with the consequent conspicuous development of microfluidic devices applied to biological and materials technology. Microfluidics has the unique advantages of the continuous flow production of multifunctional materials with accurate control of structural properties and allows distinct interplays between the surface effects, geometric confinement, viscosity parameters, and interfacial phenomena with promising applications in the LCLCs field. Recent progress in liquid crystal microfluidics has demonstrated how hydrodynamics, in combination with surface interactions, geometric confinement, and flow modulation can be harnessed to generate topological structures with potential for novel applications. , Previous works have shown that interesting phenomena are observed by precisely tuning the flow of nematic LCs, the confinement conditions in microchannels, and the wettability of channel walls. On the other hand, studies on the microfluidic generation of droplets embodying a chromonic liquid crystal and an isotropic component are still rare.…”
Section: Introductionmentioning
confidence: 99%